Reactive Neurogenesis and Down-Regulation of the Potassium-Chloride Cotransporter KCC2 in the Cochlear Nuclei after Cochlear Deafferentation - Tighilet, Brahim; Dutheil, Sophie; Siponen, Marina I.; Noreña, Arnaud J. (Frontiers in Pharmacology, 2016)
While many studies have been devoted to investigating the homeostatic plasticity triggered by cochlear hearing loss, the cellular and molecular mechanisms involved in these central changes remain elusive. In the present study, we investigated the possibility of reactive neurogenesis after unilateral cochlear nerve section in the cochlear nucleus of cats. We found a strong cell proliferation in all the cochlear nucleus sub-divisions ipsilateral to the lesion. Most of the newly generated cells survive up to one month after cochlear deafferentation in all cochlear nuclei (except the dorsal cochlear nucleus) and give rise to a variety of cell types, i.e. microglial cells, astrocytes and neurons. Interestingly, many of the newborn neurons had an inhibitory (GABAergic) phenotype. This result is intriguing since sensory deafferentation is usually accompanied by enhanced excitation, consistent with a reduction in central inhibition. The membrane potential effect of GABA depends, however, on the intra-cellular chloride concentration, which is maintained at low levels in adults by the potassium chloride co-transporter KCC2. The KCC2 density on the plasma membrane of neurons was then assessed after cochlear deafferentation in the cochlear nuclei ipsilateral and contralateral to the lesion. Cochlear deafferentation is accompanied by a strong down-regulation of KCC2 ipsilateral to the lesion at 3 and 30 days post-lesion. This study suggests that reactive neurogenesis and downregulation of KCC2 is part of the vast repertoire involved in homeostatic plasticity triggered by hearing loss. These central changes may also play a role in the generation of tinnitus and hyperacusis.